Predicting Performance in an Advanced Undergraduate Geological Field Camp Experience. Issue 4 (2nd November 2016) - Dykas, Matthew J.; Valentino, David W.
ABSTRACT: This study examined the factors that contribute to students' success in conducting geological field work. Undergraduate students ( n = 49; 51% female; mean age = 22 y) who were enrolled in the 5-wk State University of New York at Oswego (SUNY Oswego) geology field program volunteered to participate in this study. At the beginning of the field program, students completed a series of questionnaires inquiring about their academic record and their personal attitudes and beliefs. Next, participants completed a continuous series of geological field activities across 35 d in two locations in the northeastern U.S. Finally, multiple instructors independently rated students' field work performance and assigned final field program grades. Findings indicated that factors such as students' cumulative grade point averages and self-perceived preparedness for field work did not predict higher final field program grades. Instead, self-reported indices of motivation, academic self-concept, and self-efficacy predicted those grades. Moreover, evidence emerged that two domain-specific factors—intellectual orientation and achievement orientation—were uniquely associated with students' final field work grades. The implications of these findings are discussed in terms of instruction, learning, and professional employment.